Mapping Academic Resilience Profiles Among High School Students: Implications for Learning Guidance Services - Syahril, Fiqri; Muhammad Ilham Bakhtiar; Mohammad Nor Alam (ILIN Institute, 2026)
Academic resilience is an important aspect of student development that reflects how students cope with academic pressure and continue to perform despite challenges. This study aimed to describe the academic resilience profile of Grade XI students at SMA Negeri 2 Subang. A quantitative descriptive approach was applied involving 347 students from 12 classes. Data were collected using the Academic Resilience Scale based on the framework of Martin and Marsh, and analyzed using descriptive statistics such as mean, frequency, and percentage. The results show that students generally have a good level of academic resilience, although slight variations exist between classes. Overall, students demonstrate the ability to stay motivated, manage academic stress, regulate emotions, and persist in completing learning tasks despite difficulties. The findings also indicate that academic resilience is shaped not only by individual factors but also by support from family, school environment, teachers, and peers. These results highlight the importance of strengthening guidance and counseling services to support students’ adaptive learning strategies and psychological well-being in educational settings.